Knee joint kinematics during the sidestep maneuver in professional futsal athletes: Effect of sport-specific sidestep cutting - Bedo, B. L. S.; Cesar, G. M.; Vieira, L. H. P.; Catelli, D. S.; Andrade, V. L.; Santiago, P. R. P. (Science & Sports, 2022)
Introduction Futsal is characterized by a sport with a high incidence of knee injuries, especially during sidestep cutting maneuvers. Different functional tasks have been used to describe knee injury mechanisms; however, laboratory tasks must emulate the tasks performed during sports to allow for testing to be ecologically related to actual sports and practice conditions. Objective To compare knee joint kinematics of professional futsal athletes when performing the sidestep cutting maneuver with and without handling the ball. Equipment and methods Fifteen Brazilian professional futsal athletes performed three trials of anticipated 45° sidestep cutting maneuver with (SCMBALL) and without (SCM) handling a futsal ball. A tridimensional infrared camera system obtained knee joint angles (Euler angles) and angular velocity based on unit quaternions calculation. Between-tasks comparison (ball handling vs. non-ball handling) was calculated using the Student's t-test for paired samples calculated with Statistical Parametric Mapping. Results During SCM, the knee flexion angle was greater during landing preparation for both legs. During SCMBALL, a greater knee flexion angle was noted during the propulsion phase. Additionally, the inclusion of handling the ball during SCMBALL reduced knee joint velocity. No statistical significance was observed for the other variables. Conclusion The addition of handling the ball influenced knee joint kinematics, decreasing knee flexion angle at the beginning and end of the task. Knee joint velocity was also reduced. These changes can place the knee joint at a greater risk of injurious joint loading. It is suggested that future studies should include ball handling to simulate task specificity in soccer and futsal athletes.